2016
DOI: 10.18805/asd.v36i4.6470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated nutrient management on baby corn (Zea mays L.)

Abstract: A field experiment was conducted during rabi season of 2011-12 on heavy black soil to study the effect of integrated nutrient management on growth and yield of baby corn. The treatments comprising all possible combinations of five levels of nitrogen (chemical and vermicompost fertilizer) with and without bio-fertilizer (Azotobacter and PSB) were laid out in randomized block design with three replications. These were significantly higher with application of 100% RDN from chemical fertilizer with bio-fertilizer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
6
7
0
1
Order By: Relevance
“…Statistical analysis of the maize germination count revealed a substantial difference between various treatments (Table 1). The maximum germination count was recorded (151.33 plants/plot) by the application of ½ NPK + PSB + SOB, which was statistically equal to et al (2010), our results are closely in line with Jinjala et al (2016).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Statistical analysis of the maize germination count revealed a substantial difference between various treatments (Table 1). The maximum germination count was recorded (151.33 plants/plot) by the application of ½ NPK + PSB + SOB, which was statistically equal to et al (2010), our results are closely in line with Jinjala et al (2016).…”
Section: Resultssupporting
confidence: 90%
“…Findings of this study are similar with Shafiq and Tahir (2015) who was reported increase in grain proteins with the application of (PSB) Bacillus subtilis and Vesicular arbuscular mycorrhiza (VAM). Similar findings were also conveyed by Jinjala et al (2016).…”
Section: Resultssupporting
confidence: 84%
“…This result is in agreement with the findings of Atarzadeh et al (2013). This was in line with the studies of Choudhary and Jat (2004) and Jinjala et al (2016).…”
Section: Discussion Growth Attributessupporting
confidence: 92%
“…Under greenhouse conditions an increasing dose of a bovine biofertilizer made in a very similar manner as the biofertilizer Microgeo, consistently increased corn height at 60 days after sowing, most likely due the presence of nitrogen in the biofertilizer (Viana et al 2014). Regarding the integrated use of synthetic, organic and biological resources, studies addressing baby corn (Jinjala et al 2016;Dadarwal, Jain, and Singh 2009), sweet corn (Mukhlis and Lestari 2014) and corn (Singh et al 2018) reported that combining synthetic fertilizer þ biofertilizer resulted in taller plants than the application of each resource alone. Moreover, Baloach et al (2014) revealed that the application of biofertilizer alone and in combination with HA increased corn height when compared to the untreated control.…”
Section: Year 2017mentioning
confidence: 99%